2018
DOI: 10.1016/j.npe.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic brittle-ductile transition of monocrystalline sapphire during orthogonal cutting and nanoindentation experiments

Abstract: Single-crystal sapphire is utilized as a high-performance engineering material, especially in extreme and harsh environments. However, due to its extreme hardness and brittleness, the machinability of sapphire is still a challenge. By means of nanoindentation and plunge-cut experiments, the anisotropic brittle-ductile transition of the prismatic M-plane and rhombohedral R-plane is examined by analyzing crack morphologies and the critical depth-of-cut (CDC). The experimental results of the nanoindentation tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Figure 6 shows the relationship between scratch direction and (a) scratch force and (b) groove depth, respectively. Publications [ 23 , 24 , 25 ] also reported that the critical depth of cut for sapphire in the ductile-regime was less than 0.24 µm while nanoscratched depths were lower than 85 nm in this study. Therefore, the ductile-regime removal and deformation mechanisms should be discussed in this study, because all the nanoscratch experiments were completed within the ductile-regime.…”
Section: Resultssupporting
confidence: 64%
“…Figure 6 shows the relationship between scratch direction and (a) scratch force and (b) groove depth, respectively. Publications [ 23 , 24 , 25 ] also reported that the critical depth of cut for sapphire in the ductile-regime was less than 0.24 µm while nanoscratched depths were lower than 85 nm in this study. Therefore, the ductile-regime removal and deformation mechanisms should be discussed in this study, because all the nanoscratch experiments were completed within the ductile-regime.…”
Section: Resultssupporting
confidence: 64%
“…Figure (a2) and (b1) depicts the angles between lateral cracks and the ductile flow lines as approximately 20° for [−1–12] and 60° for [−110]. These cracks, forming on the groove’s outer surface due to shear stress release, differ from those within the groove surface. The presence of cracks and chips, correlating with the COF, indicates that single ductile deformation no longer solely characterizes the surface deformation under increased normal load conditions on the monocrystalline BaF 2 (111) crystal plane. Instead, it encompasses the combined effects of brittle fracture and crystal debris.…”
Section: Resultsmentioning
confidence: 99%
“…It is considered that there is a cohesive zone at the grain boundary. [1,24,30] In the dynamic damage evolution process of SCS, the action of external force overcomes the fracture energy of grain boundary surface, [1,5,6,8,18,23,24,30] causing the formation and propagation of interface crack.…”
Section: Parallel To C-axismentioning
confidence: 99%
“…The normal fracture energy of the interface is Φ n = 40 J m -2 , and the tangential fracture energy is Φ t = 6 J m -2 . [23,24,29,30,37]…”
Section: Modeling Of Cohesive Elementmentioning
confidence: 99%